Dizziness in a community hospital: central neurological causes, clinical predictors, and diagnostic yield and cost of neuroimaging studies. Issue 2 (3rd April 2017) - Ammar, Hussam; Govindu, Rukma; Fouda, Ragai; Zohdy, Wael; Supsupin, Emilio
ABSTRACT: Objectives : Neuroimaging is contributing to the rising costs of dizziness evaluation. This study examined the rate of central neurological causes of dizziness, relevant clinical predictors, and the costs and diagnostic yields of neuroimaging in dizziness assessment. Methods : We retrospectively reviewed the records of 521 adult patients who visited the hospital during a 12-month period with dizziness as the chief complaint. Clinical findings were analyzed using Fisher's exact test to determine how they correlated with central neurological causes of dizziness identified by neuroimaging. Costs and diagnostic yields of neuroimaging were calculated. Results : Of the 521 patients, 1.5% had dizziness produced by central neurological causes. Gait abnormalities, limb ataxia, diabetes mellitus, and the existence of multiple neurological findings predicted central causes. Cases were associated with gait abnormalities, limb ataxia, diabetes mellitus, and the existence of multiple neurological findings . Brain computed tomography (CT) and magnetic resonance imaging (MRI) were performed in 42% and 9.5% of the examined cases, respectively, with diagnostic yields of 3.6% and 12%, respectively. Nine cases of dizziness were diagnosed from 269 brain scans, costing $607 914. Conclusion : Clinical evaluation can predict the presence of central neurological causes of dizziness, whereas neuroimaging is a costly and low-yield approach. Guidelines are needed for physicians, regarding the appropriateness of ordering neuroimaging studies. Abbreviations : OR: odds ratio; CI: confidence interval; ED: emergency department; CT: computed tomography; MRI: magnetic resonance imaging; HINTS: Head impulse, Nystagmus, Test of skew